Vulgar Love: The Sicilian School and the New Aesthetic - Jason Collins (Vernacular: New Connections in Language, Literature, & Culture, 2020)
Much consideration has been given in the last century to the Scuola Siciliana, or the Sicilian School, the first coterie of poets in an already developed but still emergent Italian vernacular, and this in spite of an almost complete lack of autograph copies of poetic works in the original language. A great deal of this scholarship or research has a taxonomic and theoretical approach to the works, their composition, and the atmosphere that fostered them, and oftentimes attempts to position the Sicilian School within the historiography of Italian literature (particularly as progenitors to the Tuscan poets and thus Dante, Petrarch, and Boccaccio), and even European literature as a whole (as a part of the threaded continuum that includes the French Troubadour tradition, German history, and early modern Italian poetry.) Moreover, this scholarship frequently ignores the most pertinent facet of the Sicilian School’s contribution to early modernity: silent reading, or perusing language for contemplative purposes and genre development (notably the sonnet.)
Keywords: Vernacular; Medieval; Genre; Sonnet; Dialect